IN VITRO AND IN VIVO EVALUATION OF ARSENIC TRIOXIDE-LOADED NANOCREAM FOR PSORIATIC TREATMENT - Nachiketa Pandya; Neeraj Sharma (Current Research in Pharmaceutical Sciences, 2025)
Psoriasis is a chronic inflammatory skin disorder characterized by hyperproliferation and abnormal differentiation of keratinocytes, often managed with corticosteroids, which pose long-term side effects. Arsenic Trioxide, known for its antitumor and immunomodulatory properties, has shown promise in dermatological applications when formulated as a nanocream. This study aimed to formulate and evaluate Arsenic Trioxide-loaded nanocreams for their antioxidant, physicochemical, and anti-psoriatic efficacy using in vitro and in vivo models. Nanocreams were formulated with varying concentrations of Arsenic Trioxide and evaluated for physical stability, pH, viscosity, emulsion type, homogeneity, and particle size over 12 weeks. Antioxidant activity was assessed via the DPPH method. In vivo anti-psoriatic potential was tested using the mouse-tail model and UV-B-induced photodermatitis model in rats, compared against Clobetasol propionate 0.05% cream. Skin irritation tests were conducted on healthy volunteers.The 10% Arsenic Trioxide nanocream exhibited superior antioxidant activity with an IC₅₀ of 1.456 μg/mL, outperforming vitamin E. Stability tests confirmed consistent physicochemical properties over time. Particle size remained within the nanometric range (≤500 nm) for optimized formulations. No irritation was observed in human volunteers. Histopathological evaluation of skin in both mice and rats demonstrated a significant reduction in epidermal thickness and inflammatory features in groups treated with the Arsenic Trioxide nanocream, comparable to standard therapy. The Arsenic Trioxide nanocream demonstrates excellent stability, antioxidant capacity, skin compatibility, and anti-psoriatic activity, suggesting it as a promising alternative to conventional treatments for psoriasis. Key words: , , , t, DPPH, , , .